WORLD EPIDEMIOLOGY OF LEISHMANIASIS: A NARRATIVE REVIEW - Nunes, Anna Cláudia Ferreira; Ribeiro, Anna Luiza de Araújo; Aversi-Ferreira, Tales Alexandre; Aversi, Maria Tereza Mendes (Seven Editora, 2026)
Leishmaniasis is a neglected tropical disease caused by protozoa of the genus Leishmania, transmitted by the bite of infected female sandflies. Endemic in 99 countries, the disease affects more than 12 million people and represents a major global public health challenge, with World Health Organization (WHO) estimates of 30,000 new cases of visceral leishmaniasis (VL) and more than 1 million cases of cutaneous leishmaniasis (CL) annually. This study is a narrative review aimed at synthesizing the global epidemiology of leishmaniasis, with emphasis on patterns of incidence, prevalence, mortality, geographic distribution, and socioeconomic and environmental determinants of transmission. The databases consulted were PubMed, MedLine, LILACS, CAPES, PLOS and SciELO, in addition to official data from WHO and PAHO. In 2024, 85% of global VL cases were concentrated in seven countries: Brazil, Ethiopia, India, Kenya, Somalia, Sudan and South Sudan. For CL, Afghanistan, Algeria, Brazil, Colombia, Iran, Peru and Syria accounted for 83% of global incidence. The geospatial distribution of the disease is determined by ecological, sociodemographic and geopolitical factors, with systematic underreporting compromising the true magnitude of the problem. Elimination initiatives have achieved notable progress, such as Bangladesh's validation as the first country to eliminate VL as a public health problem in 2023.